Awareness and acceptability of gut microbiome transfer - Tweedie-Cullen, Ry Yves; Wilson, Brooke C.; Derraik, José G. B.; Albert, Benjamin B.; Opai, Keri; Edwards, Taygen; O’Sullivan, Justin M.; Cutfield, Wayne S. (Frontiers in Gastroenterology, 2024)
IntroductionGut microbiome transfer (GMT or faecal microbiome transfer) is gaining increasing attention as a potential treatment for a range of medical conditions. However, public awareness and acceptance are not well understood.MethodsTo better understand the public perception of microbiome transfer in New Zealand, we undertook a nationwide online survey. The anonymous survey was designed and distributed between 2022-2023. Inclusion criteria included being aged 16 years or older and a resident of New Zealand. Distribution channels included social media advertising, posters in public areas, e-mail newsletters, and a survey facilitation company.ResultsA total of 2441 completed surveys were analyzed. Most respondents (71%) had tertiary education, 59% were female, with 62% identifying as NZ European, 12% as Māori, and 3% as Pacific peoples. The findings identified a high level of awareness and acceptability, with 76% of respondents having heard of GMT, and 96% indicating they would consider it if proven efficacious for a health condition they had. High levels of acceptance were observed across all ethnicities. Encapsulated oral FMT treatment was the preferred transfer method.DiscussionPrimary concerns related to GMT included the diet, health, and screening of stool donors, as well as the demonstration of safety and efficacy. These findings will help inform health professionals and researchers about the public’s needs and preferences regarding GMT.